Beyond glycemic control: The role of Tirzepatide in MASLD and OSA management - Nabi, MD. Masud Un (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Tirzepatide, a dual GIP (glucose-dependent insulinotropic polypeptide) and GLP-1 (glucagon-like peptide-1) receptor agonist, represents a breakthrough in the treatment of metabolic disorders. While primarily developed for type 2 diabetes and weight management, its benefits extend beyond glycemic control to conditions like Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) and Obstructive Sleep Apnea (OSA). Similarly, OSA—a condition characterized by recurrent upper airway obstruction during sleep—is worsened by excess visceral fat and inflammation. Clinical studies, including the SURPASS and SURMOUNT trials, indicate that Tirzepatide leads to substantial weight loss and improved apnea-hypopnea index (AHI), suggesting a direct role in mitigating OSA severity. By targeting core mechanisms such as obesity, insulin resistance, and inflammation, Tirzepatide offers a comprehensive therapeutic strategy for patients with coexisting metabolic diseases. Ongoing research aims to determine whether its effects on MASLD and OSA are independent of weight loss. Tirzepatide is emerging as a multifaceted agent capable of transforming the management of obesity-related complications, offering new hope for patients with MASLD and OSA. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S29]